Notes and additions about the genus Orthocladius s. str. (Diptera Chironomidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
Orthocladius mariellae Rossaro & Prato is here stated as junior synonym of O. rivinus Kieff. O. rachelae Rossaro & Prato is stated as junior synonym of O. wetterensis Brundin. According to Langton & Cranston (1991), O. pinderi Rossaro & Prato should become a junior synonym of O. oblidens Walker. The species are here considered as distinct valid species, because the anal point of adult male is markedly different in the two species. O. ruffoi Rossaro & Prato is a valid species, identical with Rheorthocladius sp. A. Thienemann, already known in the pupal stage.
Keywords: Orthocladius spp.; Chironomidae; Diptera Nematocera